FAKTOR-FAKTOR PENYEBAB GANGGUAN MENTAL EMOSIONAL PADA REMAJA DI KOTA PEKALONGAN - Hanwaring Puri, Citra; Shaluhiyah, Zahroh; Arso, Septo Pawelas (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Adolescence is a critical period to improve mental health. The prevalence of emotional mental disorders in Indonesia is quite high, at 33.3%. This study aimed to find out the factors that affect adolescent mental emotional disorders in Pekalongan City. This research was a cross-sectional research, data collection using questionnaires. The population in this study is high school students aged 15-18 years in Pekalongan City with a total of 3,080 students. The sampling technique was carried out by proportional random sampling with a total of 360 respondents.Data analysis used the spearman rank test. The results of the study showed that the factors that affect mental emotional disorders in adolescents in Pekalongan City are: perception of bullying level (ρ-value = 0.00), intensity of social media use (ρ-value = 0.00), parenting style (ρ-value = 0.00), lifestyle (ρ-value = 0.00) and the implementation of early detection of adolescent mental health (ρ-value = 0.005). The causes of mental and emotional disorders in adolescents in Pekalongan City are the perception of bullying level, intensity of social media use, parenting style, lifestyle and the implementation of early detection of adolescent mental health. The Pekalongan City Health Office needs to make efforts to improve adolescent mental health such as anti-bullying programs in schools, socialization of adolescent mental health for adolescents and parents conventionally and digitally, and increasing the coverage of early detection of adolescent mental health.